Management of Crohn's Disease in the New Era of Gut Rehabilitation and Intestinal Transplantation. Issue 7 (July 2016) - Nyabanga, Custon; Kochhar, Gursimran; Costa, Guilherme; Soliman, Basem; Shen, Bo; Abu-Elmagd, Kareem
Abstract : Abstract: Despite recent therapeutic advances, patients with Crohn's disease (CD) continue to experience high recurrence with cumulative structural damage and ultimate loss of nutritional autonomy. With short bowel syndrome, strictures, and enteric fistulae being the underlying pathology, CD is the second common indication for home parenteral nutrition (HPN). With development of intestinal failure, nutritional management including HPN is required as a rescue therapy. Unfortunately, some patients do not escape the HPN-associated complications. Therefore, the concept of gut rehabilitation has evolved as part of the algorithmic management of these patients, with transplantation being the ultimate life-saving therapy. With type 2 intestinal failure, comprehensive rehabilitative measures including nutritional care, pharmacologic manipulation, autologous reconstruction, and bowel lengthening is often successful, particularly in patients with quiescent disease. With type 3 intestinal failure, transplantation is the only life-saving treatment for patients with HPN failure and intractable disease. With CD being the second common indication for transplantation in adults, survival outcome continues to improve because of surgical innovation, novel immunosuppression, and better postoperative care. Despite being a rescue therapy, the procedure has achieved survival rates similar to other solid organs, and comparable to those who continue to receive HPN therapy. With similar technical, immunologic, and infectious complications, survival is similar in the CD and non-CD recipients. Full nutritional autonomy is achievable in most survivors with better quality of life and long-term cost-effectiveness. CD recurrence is rare with no impact on graft function. Further progress is anticipated with new insights into the pathogenesis of CD and mechanisms of transplant tolerance. Abstract : Article first published online 22 April 2016.